Constructing Inclusive Classroom Climates: An Interpretive Study of Social-Emotional Learning Integration in Pakistani Elementary Education - Bokhari, Tahira Batool; Anis, Faisal; Muhammad, Yaar (Regional Lens, 2025)
This interpretive study examines how elementary school teachers in Pakistan construct inclusive classroom climates through the integration of social-emotional learning. Using the assertion development methodology proposed by Erickson, the study was conducted with a sample of 12 teachers working in an elementary school. The researchers identified five main claims: that climate is built by micro-interactions between teachers rather than the official curriculum; that resource regulation implies improvisational climate-building practices; that shared cultural values construct climates differently than individualistic models; that peer relations are the core climate formation process; and that teachers affective states are the most basic way of creating an emotional climates in a classroom. The findings highlight the gap between the expectations of an inclusive education policy and the real-life situations faced by teachers in Pakistani elementary settings. The study also has methodological contributions because it shows the utility of assertion development in explaining the complex phenomenon of pedagogical and has practical contributions in identifying the leverage points of helping the climate development work of teachers.